The Prevalence of Post-traumatic Stress Disorder (PTSD) Symptoms in Women Hospitalized Due to COVID-19 Infection during Pregnancy in Indonesia and Its Association with Employment Status and Delivery Method: A Single Center Study - Sarkoen, Widyastuti; Hertika, Amanda; Deliandra, Irfan; Pitawati, Dian; Puspita, Neza; Manurung, Reza Tigor (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective: To analyze the prevalence of post-traumatic stress disorder (PTSD) symptoms in pregnant women infected with COVID-19 in one of the Indonesian tertiary referral centers for COVID-19 cases and its association with maternal employment status and delivery method. Method: Data from medical records and an online questionnaire were collected for a cross-sectional study. The study included pregnant women treated in the COVID-19 non-intensive isolation wards throughout 2021. The occurrence of PTSD symptoms was assessed using the PTSD Checklist for DSM-5 (PCL-5). Prevalence of PTSD symptoms was decribed and its correlation with employment status and delivery method were analyzed. Results: The analysis involved data from 75 patients, with a mean PCL-5 total score of 17 ± 13.85. Among them, 16% met the PTSD symptoms criteria (PCL-5 total score more than 32). Of the total, 72% were women who had undergone caesarean section (CS), and the same percentage were unemployed. Comparisons revealed no significant difference in PTSD symptoms occurence based on employment status (19% in employed women vs. 14.8% in unemployed women, p=0.729, 95% CI) and delivery method (14.8% in CS vs. 16.7% in spontaneous delivery, p=1, 95% CI). Conclusion: This study revealed a significant prevalence of PTSD among pregnant women during the COVID-19 pandemic. Despite there is no association found between the prevalence of PTSD symptoms and employment status or delivery method in this study, further research is needed to understand the psychological effects, clinical implications, and relevant factors impacting pregnant women in the acute-event settings. Keywords: COVID-19, pandemics, pregnancy, post-traumatic stress disorders